Physical Therapy and Maternity Support Garment: Influence on Core Stability and Low Back Pain during Pregnancy and after Delivery (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Transversus abdominis muscle experiences extraordinary overstretching during gestation period and thus the ability of this muscle to stabilize spine decreases. These changes can cause chronic low back pain during pregnancy and after delivery. In order to solve this problem it is essential to apply proper and effective treatment methods. Hypothesis: physical therapy exercises are more effective than maternity support garment in low back pain treatment and core stability during pregnancy and after delivery.Research aim was to evaluate the influence of physical therapy and maternity support garment on spinal stability and low back pain during pregnancy and after delivery.Research methods. Study sample comprised 40 pregnant women. The assessments were made twice: at 28–35 weeks of gestation and 8–9 weeks after delivery. The low back pain was evaluated using SAS, core stability and transversus abdominis muscle activation were objectively tested using special device stabilizer and the presence of diastasis recti was tested as well. Research results. Physiotherapy is 42.4% more effective than maternity support garment in low back pain control during pregnancy and after delivery (p < 0.05). The best results of transversus abdominis muscle activation were observed in physiotherapy group with maternity support garment whereas participants without physiotherapy could not properly activate this muscle. The diastasis recti after delivery occurred only in control group, and in the group with maternity support garment it occurred 36.7% less frequently than in the group where women did not use this garment.Discussion and conclusions. 1. Perceived low back pain after delivery was less expressed in women wearing maternity support garment both among women attending and not attending physiotherapy exercises. Nevertheless, physical therapy was more effective in reducing low back pain than maternity support garment during pregnancy and after delivery. 2. Core stability after delivery improved among women attending physical therapy exercises, but in case of maternity support garment it improved better. In contrast, in case of not attending physiotherapy the spinal stability after delivery improved only for women wearing maternity support garment. 3. Core stability during pregnancy and after delivery was better among women attending physical therapy but not wearing maternity support garment compared to women not attending physical therapy but wearing maternity support garment. 4. Physical therapy and maternity support garment improves core stability during pregnancy and has a positive effect on activity of rectus abdominis muscles following delivery.Keywords: obstetrics, transversus abdominis muscle, exercises.